Técnicas intervencionistas de recuperação ecológica em áreas florestais e influências nas características físicas, químicas e isotópicas dos solos - Valle, Leandro Dalla [UNESP] (2015)
Soils under commercial reforestation of exotic tree species suffer several physical-chemical changes, which has been seen as major importance by companies and researches, aiming evaluate how enviornmental recovery techniques influence the soil indicators. Thereby, the soil quality was assessed investigating the physical, chemical and isotopic soil attributes and the soil organic matter (SOM), in stands submitted to three environmental restoration techniques: soil litter transposition of adjacent areas (stand T), stopping of forest management activities (stand E), and perches (stand P), and also a stand where occurs semideciduous seasonal forest (stand reference - R). The four stands are located in a farm in Bofete city of São Paulo state. In each stand, soil samples were collected in five thicknesses. The samples were dried, sieved and delivered to laboratories for chemical and isotopic analyses. The chemical attributes were related to soil pH, which indicated high acidity in all layers. The ð13C values in the superficial layer of the soil were smaller for the R and E stands, indicating predominance of C3 vegetation. The values of ð15N were smaller throughout the soil profile only in the R stand, pointing out response of the soil to former chemical fertilizations. The concentrations of both carbon (C) and nitrogen (N) in all managed stands were smaller than the R stand. In conclusion analyzing the soil by means of C and N isotopic signatures was an important tool to assess SOM quality. In comparison with data go from R stand, the E stand presented the best indicators. As a complementary activity in projects of enviornmental restoring, it is encouraged limiting and phosphate fertilization